Participatory information governance: Transforming recordkeeping for childhood out-of-home Care. (15th January 2019) - Evans, Joanne; McKemmish, Sue; Rolan, Gregory
Abstract : Purpose: This paper examines the recordkeeping governance requirements of the childhood out-of-home Care sector, with critical interlaced identity, memory, cultural and accountability needs. They argue that as we enter a new era of participation, new models for governance are required to recognise and dynamically negotiate a range of rights in and to records, across space and through time. Instead of recordkeeping configured to support closed organisations and closely bounded information silos, there is a need for recordkeeping to reflect, facilitate and be part of governance frameworks for organisations as nodes in complex information networks. Design/methodology/approach: The paper reports on a key outcome of the Setting the Record Straight for the Rights of the Child National Summit held in Melbourne Australia in May 2017, the National Framework for Recordkeeping in Out-of-Home Care, and the research and advocacy agenda that will support its development. Findings: The authors argue that as we enter an algorithmic age, designing for shared ownership, stewardship, interoperability and participation is an increasing imperative to address the information asymmetries that foster social disadvantage and discrimination. The authors introduce the concept of participatory information governance in response to social, political and cultural mandates for recordkeeping. Given the challenges associated with progressing new participatory models of recordkeeping governance in the inhospitable environment of existing recordkeeping law, standards and governance frameworks, the authors outline how these frameworks will need to be re-figured for participatory recordkeeping. Practical implications: The National Framework for Recordkeeping for Childhood Out-of-Home Care seeks to address the systemic recordkeeping problems that have been most recently highlighted in the 2013-2017 Royal Commission into Institutional Responses to Child Sexual Abuse. Social implications: The National Framework for Recordkeeping for Childhood Out-of-Home Care will also address how a suite of recordkeeping rights can be embedded into networked socio-technical systems. This represents an example of a framework for participatory information governance which can help guide the design of new systems in an algorithmic age. Originality/value: The proposed National Framework represents a new model for recordkeeping governance to recognise and enact multiple rights in records. Designed to support the lifelong identity, memory and accountability needs for those who experience childhood out-of-home Care, it aims to foster the transformation of recordkeeping and archival infrastructure to a participatory model that can address the current inequities and better enable the design and oversight of equitable algorithmic systems.